(untitled) (Eurasian Research Bulletin, 2022)
The methodological application of the number series of words in Uzbek folk epics and the comprehensive analysis of words related to the number series of words, their application in any sense, as well as the definition, analysis of the stylistic expression, as well as to determine the sides of the meaning of words related to the number series and to have excellent information about this.